Analysis of capacity load and nutritional status of peritoneal dialysis patients with diabetic kidney disease and non diabetic kidney disease - BAI Tian-li; YU Qing; ZHU Bing-bing; WANG Yun-man; WANG Hao (Linchuang shenzangbing zazhi)
Objective To analyze the changes of capacity load and nutritional status of diabetic kidney disease(DKD) and non diabetic kidney disease(NDKD) patients within one year of peritoneal dialysis,so as to provide theoretical basis for better clinical intervention.Methods The general data of 116 patients(42 in DKD group and 74 in NDKD group) who received peritoneal dialysis(PD) in our hospital from January 2010 to August 2019 were collected by retrospective analysis.The indexes of laboratory tests such as liver function and brain natriuretic peptide were measured at baseline and 1,3,6,12 months after PD;and clinical evaluation indexes such as peritoneal dialysis mode,dialysate concentration and dosage,24-hour ultrafiltration volume,24-hour urine volume,blood pressure,edema,and types of antihypertensive drugs were compared within a group and between groups by statistical tools,so as to clarify PD efficacy and the efficacy difference between the two groups.Results The dosage of peritoneal dialysis in the DKD group was higher than that in NDKD group(P<0.05) at various time points one month after dialysis.There was no significant difference in 24-hour peritoneal ultrafiltration volume(P>0.05),but 24-hour urine volume in the DKD group was less than that in the NDKD group(P<0.05),the incidence of edemat was higher than that of NDKD group(P<0.05) after 12 months of dialysis,but there was no significant difference in blood pressure level and types of antihypertensive drugs taken(P>0.05).After treatment,serum albumin(Alb) in the study population was lower than that at baseline(P<0.05),and Alb in the DKD group was lower than that in the NDKD group(P<0.05) from baseline to six months after dialysis.There was no significant difference between the two groups after six months(P>0.05).Conclusions The nutritional status in the DKD group is worse than that in the NDKD group at the early stage of dialysis.After 12 months of dialysis,the patients in the DKD group are in a higher capacity load condition than those in the NDKD group.After 1 month of dialysis,the DKD group needs a bigger peritoneal dialysis dosage than the NDKD group.This suggests that clinicians should make a reasonable peritoneal dialysis plan according to their body fluid retention,blood pressure and other factors to maintain an appropriate blood volume and protect residual renal functions.